The safety of anaesthesia delivered by rural generalist anaesthetists: a scoping review of the literature - Peter Gilchrist; Lucie Walters; Paul Ward (James Cook University, 2023)
Introduction: Rural generalist anaesthetists (RGAs) are central to the delivery of health care in much of rural and remote Australia. This article details a systematic review of the literature specifically asking the question, 'What is the current evidence of the 'safety' of anaesthesia delivered by RGAs?' Methods: Six databases were searched using terms including 'safety', 'rural', 'anaesthetics', 'general practitioners', and associated search terms. Relevant articles were assessed for rigour, and information was summarised using qualitative grid analysis that included information on the study setting, participants, methods, limitations and key result areas. The primary author developed key themes from the data, which were refined in discussion with other authors. Results: The safety of RGAs was described using five concepts: appropriate training and leadership, rates of complications, volume or scope of practice, access to equipment, and case selection. Conclusion: RGAs are pivotal in the delivery of health care in rural and remote communities. The sparse literature available on RGA safety is broadly grouped into five areas. There is a need to characterise and describe the role of RGAs, review and revise training and education, recognise RGA scope of practice and understand how RGAs lead the management of safety and risk in their practice.